Factors Influencing Consumer Behaviour Intention to Purchase Fast Food: a Study of McDonald’s in Malaysia - Singh, Dr. Kavita; Tan, Joe Fen; Binti Abdullah, Syaza Afiqah; Tan, Hui Mei; Tan, Zhiwen; Fauziah, Nurafikatul; Sharma, Sakshi; Kee, Dr. Daisy Mui Hung (Journal of The Community Development in Asia, 2023)
McDonald’s, as the largest worldwide retailer of foodservice, has more than 38,000 locations across more than 100 countries. The company's mission is to quickly adapt to generate profitable growth and to improve upon McDonald's in order to serve superior and high-quality meals to more people every day around the world. The study was conducted to identify and analyze the factors influencing consumer behaviors intention to purchase in the fast-food sector (McDonald's). We investigate whether product and service quality, pricing, promotion, brand awareness, restaurant surrounding and environment will affect the consumers’ behaviour to purchase fast food at McDonald's. Besides, the research that we conducted also related to Sustainable Development Goals (SDGs) as McDonald's has presented its corporate responsibilities. For the study, both primary and secondary data were collected from multiple sources and a digital questionnaire (via Google Form) was created to collect data and information from 150 respondents. Recommendations and implications were discussed.